Pengaruh Model Pembelajaran Contextual Teaching Learning Berbasis Video terhadap Kemampuan Berpikir Kreatif Pembelajaran Bahasa Indonesia Siswa Kelas V SDN Gunung Sari II Makassar - Muh Niamur Ridho; M. Agus; Nur Khadijah Razak (Journal on Education, 2024)
This research aims to determine the creative thinking abilities of fifth grade students at SDN Gunung Sari II Makassar in learning Indonesian after using the Video-Based Contextual Teaching Learning Model and the influence of using the Video-Based Contextual Teaching Learning Model on students' creative thinking abilities in class students' Indonesian language learning. V SDN Gunung Sari II Makassar. This research uses the Experimental Design research method. The population in this study were all class V students at SDN Gunung Sari II Makassar. The sampling technique used was a total sampling technique or saturated sampling with experimental class and control class samples. The instrument used is a test instrument in the form of essay questions to measure student learning outcomes with Pretest - Posttest Control Group Design. Based on the research results, it shows that the Pancasila Education learning outcomes of students in the experimental class after using the Video-Based Contextual Teaching Learning Model were 100% in the very creative category, while in the control class it was 87.5% in the creative category. Meanwhile, the effect of using the Video-Based Contextual Teaching Learning Model on the ability to think creatively in learning Indonesian for class V students at SDN Gunung Sari II from the results of hypothesis management obtained Sig (2.Tailed) = 0.000, meaning that H0 is rejected because Sig (2.Tailed) < α or (0.000 < 0.05). H1 is accepted because Sig (Tailed) > α or (0.788 > 0.05) with the results of the T test analysis, Sig < ttable or (0.392 < 1.753). So the influence of using the Video-Based Contextual Teaching Learning Model on students' creative thinking abilities in learning Indonesian for class V students is influential at SDN Gunung Sari II Makassar.